Rhetorics of democracy in the Americas - Angel, Adriana, 1981-; Butterworth, Michael L.; Gómez, Nancy R. (Nancy Regina), 1978- (Rhetoric and democratic deliberation, 2021)
"A collection of essays examining the rhetorics that underlie democratic politics in Latin America and the United States"--